Malicious data classification in packet data network through hybrid meta deep learning - Tapu, Sakib Uddin; Alam Shopnil, Samira Afrin; Tamanna, Rabeya Bosri (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.